Comparative evaluation of cost-effectiveness between typical antipsychotic haloperidol and atypical antipsychotics olanzapine, risperidone and aripiprazole in the treatment of stable schizophrenia - Vishal, Subhash; Beg, Mirza A.; Dutta, Shakti B.; Khatri, Sumit; Garg, Shobhit; Singh, Nand Kishore; Kaur, Amanjot (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Schizophrenia patients mostly require life-long treatment. For such long-term treatments, cost is an important factor. Estimate of cost in terms of efficacy can give idea to prescribers about the relative financial burden posed by various typical and newer antipsychotics in schizophrenic patients. Methods: A total of 98 stable schizophrenic patients were enrolled in this open label study over a period of 1 year. Patients were divided in four groups, group-I received Haloperidol (n=24), group-II received Olanzapine (n=25), group-III received Risperidone (n=25) and group-IV received Aripiprazole (n=24). The patients were given drugs on the basis of physician’s discretion, depending upon the condition of the patient at the time of presentation. Patients were followed up to 16 weeks. Direct treatment costs and efficacy of treatment in terms of Clinical Global Impression - Efficacy Index CGI (EI) noted and average cost-effectiveness worked out. Results: In this open label study, the mean age of patients was 35.05±1.30. The average cost-effectiveness ratio was 26.25 for haloperidol, 10.12 for Olanzapine, 9.83 for Risperidone and 25.92 for Aripiprazole. Conclusions: Risperidone was found to be most cost-effective, followed by olanzapine, then by aripiprazole, whereas haloperidol was found least cost effective.